Trends in the F2 ionospheric layer due to long-term variations in the Earth's magnetic field - Elias, Ana Georgina (2009)
The Earth's magnetic field presents long-term variations with changes in strength and orientation. Particularly, changes in the dip angle (I) and, consequently, in the sin(I)cos(I) factor, affect the thermospheric neutral winds that move the conducting plasma of the ionosphere. In this way, a lowering or lifting of the F2-peak (hmF2) is induced together with changes in foF2, depending on season, time and location. A simple theoretical approximation, developed in a previous work, is extended to a worldwide latitude–longitude grid to assess hmF2 and foF2 trends due to Earth's magnetic field secular variations. Compared to the greenhouse gases effects over the ionosphere, the Earth's magnetic field may be able to produce stronger trends which vary with season, time and location. However, to elucidate the origin of F2-region trends, long-term variations in the three possible known mechanisms should be considered altogether—greenhouse gases, geomagnetic activity and Earth's magnetic field.